2002
DOI: 10.1128/aem.68.9.4502-4508.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid Stimulates Uptake of Hydrophobic Compounds by Pseudomonas aeruginosa

Abstract: The biodegradation of hexadecane by five biosurfactant-producing bacterial strains (Pseudomonas aeruginosa UG2, Acinetobacter calcoaceticus RAG1, Rhodococcus erythropolis DSM 43066, R. erythropolis ATCC 19558, and strain BCG112) was determined in the presence and absence of exogenously added biosurfactants. The degradation of hexadecane by P. aeruginosa was stimulated only by the rhamnolipid biosurfactant produced by the same organism. This rhamnolipid did not stimulate the biodegradation of hexadecane by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 36 publications
1
81
0
Order By: Relevance
“…For this purpose, we used P. aeruginosa, which produces surfactants and secretes lipases, allowing it to solubilize and take up very hydrophobic compounds (43).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we used P. aeruginosa, which produces surfactants and secretes lipases, allowing it to solubilize and take up very hydrophobic compounds (43).…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas is the best-known bacteria capable of using hydrocarbon as an energy source and producing biosurfactants [31][32][33]. Pseudomonas aeruginosa has been widely studied and is known to produce a glycolipid type of biosurfactant [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in another study that n-hexadecane was attracted to the cell surface of the 21 BN strain of P. putida at a rate of 72% (Tuleva et al, 2002). In a study by Noordman and Janssen (2002) at rates of 42%, 81%, 30%, and 12%, respectively. Similarly, it was observed that G1 strains of P. aeruginosa degraded 48% of 2.5% crude oil in 7 days (Celik et al, 2008).…”
Section: Emulsification Activity and Cell Surface Hydrophobicitymentioning
confidence: 92%